User allocation technology for multi-dimensional resource optimization of LEO satellite - ZHOU Jiaen; ZHAO Yafei; PENG Mugen (Dianxin kexue)
Low earth orbit (LEO) satellite communication technology can provide ground users with broad coverage, high capacity, and high reliability services, making it one of the key supporting technologies for future networks. Direct-to-mobile satellite communication technology offers advantages such as portability, low cost, and large user scalability, promising extensive commercial and application prospects. Simultaneously, it generates corresponding demand for service resources from LEO satellite. In scenarios where LEO satellite resources were constrained, a service model was proposed that comprehensively considers communication, sensing, computation, and storage. Based on this model, a user allocation method was proposed. Simulation results indicate that this strategy, compared to three other methods, achieves higher resource utilization rates, serves more mobile phone users, and provides theoretical support for the development of direct-to-mobile satellite communication technology.